Fluorescence and FTIR Spectra Analysis of Trans-A2B2-Substituted Di- and Tetra-Phenyl Porphyrins - Sen, Pinar; Hirel, Catherine; Andraud, Chantal; Aronica, Christophe; Bretonniere, Yann; Mohammed, Abdelsalam; Agren, Hans (Mdpi Ag, 2010)
A series of asymmetrically substituted free-base di- and tetra-phenylporphyrins and the associated Zn-phenylporphyrins were synthesized and studied by X-ray diffraction, NMR, infrared, electronic absorption spectra, as well as fluorescence emission spectroscopy, along with theoretical simulations of the electronic and vibration structures. The synthesis selectively afforded trans-A(2)B(2) porphyrins, without scrambling observed, where the AA and BB were taken as donor-and acceptor-substituted phenyl groups. The combined results point to similar properties to symmetrically substituted porphyrins reported in the literature. The differences in FTIR and fluorescence were analyzed by means of detailed density functional theory (DFT) calculations. The X-ray diffraction analysis for single crystals of zinc-containing porphyrins revealed small deviations from planarity for the porphyrin core in perfect agreement with the DFT optimized structures. All calculated vibrational modes (2162 modes for all six compounds studied) were found and fully characterized and assigned to the observed FTIR spectra. The most intense IR bands are discussed in connection with the generic similarity and differences of calculated normal modes. Absorption spectra of all compounds in the UV and visible regions show the typical ethio type feature of meso-tetraarylporphyrins with a very intense Soret band and weak Q bands of decreasing intensity. In diphenyl derivatives, the presence of only two phenyl rings causes a pronounced hypsochromic shift of all bands in the absorption spectra. Time-dependent DFT calculations revealed some peculiarities in the electronic excited states structure and connected them with vibronic bands in the absorption and fluorescence spectra from associated vibrational sublevels.
Keywords: tetraphenyl porphyrin; asymmetric substitution; electronic structure; TD DFT; FTIR; fluorescence